(untitled) (Research, Society and Development, 2020)
This article aims to raise the profile of the Pará prison population in the pandemic of the new Coronavirus, which causes the disease COVID-19, called SARS-CoV-2, from January to September 2020. A review of the literature relevant to the theme and an exploratory-descriptive research was carried out, with a quantitative approach, with analysis of secondary data available in the databases of the Secretariat of Penitentiary Administration (SEAP), National Council of Justice (CNJ), National Council of the Public Prosecutor’s Office (CNMP) and the National Prison Information Survey (INFOPEN). The results show that the Paraense Prison System has a deficit of 5,569 vacancies. Regarding the COVID-19 data, it presents 666 confirmed cases, 84 suspects, 97 under treatment and no deaths. 1,500 tests were carried out to detect COVID-19 among persons deprived of their liberty (PPLs) and 55 isolation beds were made available for observation of suspected COVID-19. There was a percentage increase in medical care to the prison population of the State of Pará in the months from January to August 2020, when compared to the same period in 2019. It is concluded that the positive result of the non-occurrence of deaths from PPLs points to an efficiency in facing the spread of infection by the new Coronavirus in the paraense prison system, however the low rate of testing for detection of Covid-19 may indicate underreporting and ignorance of the real dimension of the pandemic.